Infodemiology of Rabies in Indonesia and Neighboring Countries: Insights from Google Trends (2020–2024) - Agil Wahyu Wicaksono; Fatiha Kamilah; Dinda Iryawati (Epidemiology and Society Health Review (ESHR), 2026)
Background: As Asian countries struggle to meet the global "Zero by 30" rabies target due to delayed and underreported conventional surveillance, digital infodemiology offers a complementary solution. This study analyzes rabies-related Google Trends search interest in Indonesia, Malaysia, the Philippines, Thailand, and Vietnam from 2020 to 2024 to evaluate its utility for public health monitoring and elimination strategies. Method: Google Trends was queried for the term "rabies" across the five countries from January 2020 to December 2024. Monthly normalized scores (0–100) were collected and analyzed descriptively. Trends were examined at monthly and annual levels, including seasonal fluctuations and exceptional peaks. Relative growth between 2020 and 2024 was calculated to identify shifts in long-term public awareness. Results: Thailand consistently demonstrated the highest baseline search interest, while Indonesia remained the lowest despite a dramatic spike in June 2023 (score 100). Seasonal increases were observed in Thailand and Vietnam during the second half of the year, coinciding with agricultural cycles and awareness campaigns. Annual mean scores rose in all countries, with the Philippines showing the largest relative increase (+164%), followed by Indonesia (+110%). Malaysia and Vietnam exhibited moderate growth, while Thailand's increase was more modest (+86%). Conclusion: Rabies awareness in Southeast Asia is highly variable and largely event-driven, highlighting the need for integrated, sustained communication strategies tailored to each country's epidemiological and sociocultural context to support the achievement of the "Zero by 30" elimination goal.